Peningkatan Kemampuan Membaca Al-Qur’an: Metode Tartil Bagi Anak Mengaji di Desa Ulu Aer Kecamatan Sosopan - Alwi Hamdani Hasibuan,; Hotma Sari Hasibuan,; Nur Hapni Hasibuan,; Abdul Rohit Hasibuan,; Agustina Lubis,; Putri Hasanah Kasih Nasution, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Reading the Qur'an is the main guideline to calm the hearts of Muslims, and is one of the worship that must be done to obtain the pleasure of Allah SWT, indeed does not prioritize absorption and understanding through the transfer of information alone, but rather prioritizes the development of skills. For this reason, the abilities of students need to be developed through active roles and exercises or activities that can support the ability to read the Qur'an. The tartil method is a way of reading the Qur'an slowly and slowly and pronouncing the letters from the makhraj correctly. Reading slowly and correctly can clearly hear each letter, and its tajweed. This study aims to: (1) Determine and describe the application of the Tartil method to improve children's understanding in reading the Qur'an correctly according to the rules of makhraj and the laws of reading it for children in Ulu Aer village, (2) To determine and describe the increase in the ability to read the Qur'an after using the Tartil method in children in Ulu Aer village. The author conducted descriptive research, collecting data through direct research, documentation, and interviews. The author concluded that the use of tartil would improve children's understanding of the Quran in Ulu Aer village.